Electronic Engineering of ABO3 Perovskite Metal Oxides Based on d0 Electronic‐Configuration Metallic Ions toward Photocatalytic Water Splitting under Visible Light. Issue 6 (25th March 2022) - Bao, Yunfeng; Zhang, Fuxiang
Abstract : Particulate photocatalytic water splitting is considered as one of the most promising and low‐cost routes toward green hydrogen production, toward which developing a semiconductor photocatalyst with a wide visible light response and high charge transfer velocity is the key issue. Metal oxides based on d 0 ‐configuration metal ions, especially those with the perovskite structure, are a group of ideal candidates toward photocatalytic water splitting, benefitting from their high structural stability, suitable conduction band minimum (CBM), and high carrier mobility. However, the main problems staggering the development of highly efficient photocatalysts are from the rather big bandgap of these d 0 ‐configuration metal oxides to cause limited UV light response and from the flexibly changed valence state of the d 0 ‐configuration metal cations in the B site of the perovskite structure. Various strategies are developed to address these problems, and the summary on electronic engineering strategies of the d 0 ‐metal‐based perovskite metal oxides toward visible light response and stable photocatalytic performance in this review is focused on. Finally, the construction of the photocatalytic overall water splitting (OWS) system based on these perovskite semiconductors is discussed and outlooked. Abstract : The electronic engineering strategies of the d 0 ‐metal‐based perovskite metal oxides toward visible light response and stable photocatalytic performance are focused on in this review. The construction of the photocatalytic overall water splitting (OWS) system based on these perovskite semiconductors is discussed and outlooked.